2015
DOI: 10.1007/s00406-015-0634-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oxytocin augmentation therapy for schizophrenia: an updated systematic review and meta-analysis of randomized, placebo-controlled trials

Abstract: The aim of this study was to perform a systematic review and an updated and comprehensive meta-analysis of oxytocin augmentation therapy in patients with schizophrenia who received antipsychotic agents. Data published up to 07/11/2015 were obtained from PubMed, PsycINFO, and Cochrane Library databases. We conducted a systematic review and meta-analysis of patients' data from randomized controlled trials (RCTs) comparing oxytocin with placebo. Relative risk (RR), standardized mean difference (SMD), and 95 % con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…While these findings need to be interpreted cautiously given the post hoc nature of the analyses, the data suggest a potential advantage for oxytocin on negative symptoms. This is also consistent with a recent meta-analysis which found that, among consecutive-day dosing studies (6 studies, N=192 participants), oxytocin demonstrated significant improvement in negative symptoms in people with schizophrenia (Oya et al, 2015). In addition, Cacciotti-Saija et al (2014) reported a significant dose-response relationship between oxytocin and negative symptoms, suggesting a modest therapeutic effect that was not demonstrated for other symptom domains.…”
Section: Discussionsupporting
confidence: 90%
“…While these findings need to be interpreted cautiously given the post hoc nature of the analyses, the data suggest a potential advantage for oxytocin on negative symptoms. This is also consistent with a recent meta-analysis which found that, among consecutive-day dosing studies (6 studies, N=192 participants), oxytocin demonstrated significant improvement in negative symptoms in people with schizophrenia (Oya et al, 2015). In addition, Cacciotti-Saija et al (2014) reported a significant dose-response relationship between oxytocin and negative symptoms, suggesting a modest therapeutic effect that was not demonstrated for other symptom domains.…”
Section: Discussionsupporting
confidence: 90%
“…Both medications are associated with mild side effect profiles (Hansen et al, 2008; Oya et al, 2016), are relatively inexpensive, and have shown efficacy in at least some studies (Lee et al, 2013). Unfortunately, data from the CIDAR trial failed to find significant improvements in negative symptom severity or cognitive functioning with either galantamine or oxytocin compared to placebo using standard clinical rating scales or neuropsychological test batteries (Buchanan et al, 2016).…”
Section: Dear Editormentioning
confidence: 99%
“…They also coded two Brief Psychiatry Reporting Scale (BPRS) outcomes as general psychopathology. Based on the contents of the scale and other meta-analyses on this topic (Oya et al, 2015), this should have either been coded as psychotic symptoms or they should have provided rationale for divergent coding. All four of these outcomes were reported as positive which, in addition to the aforementioned errors, likely inflated their meta-analytic estimates.…”
Section: Misspecified Outcomesmentioning
confidence: 99%